2017
DOI: 10.1002/sctm.16-0474
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Cord Blood Infusions Are Safe and Feasible in Young Children with Autism Spectrum Disorder: Results of a Single-Center Phase I Open-Label Trial

Abstract: Despite advances in early diagnosis and behavioral therapies, more effective treatments for children with autism spectrum disorder (ASD) are needed. We hypothesized that umbilical cord blood‐derived cell therapies may have potential in alleviating ASD symptoms by modulating inflammatory processes in the brain. Accordingly, we conducted a phase I, open‐label trial to assess the safety and feasibility of a single intravenous infusion of autologous umbilical cord blood, as well as sensitivity to change in several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(108 citation statements)
references
References 29 publications
3
101
1
1
Order By: Relevance
“…In children with cerebral palsy (motor disorder in childhood), autologous hUCMSCs improved whole brain connectivity and motor function . Similar studies found that infusion of autologous cord blood cells in children with autism spectrum disorder improved behavior and was safe . A 6‐year follow‐up study also demonstrated the long‐term safety profile of hUCMSCs infusion for drug‐resistant systemic lupus erythematosus patients.…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticsupporting
confidence: 59%
See 1 more Smart Citation
“…In children with cerebral palsy (motor disorder in childhood), autologous hUCMSCs improved whole brain connectivity and motor function . Similar studies found that infusion of autologous cord blood cells in children with autism spectrum disorder improved behavior and was safe . A 6‐year follow‐up study also demonstrated the long‐term safety profile of hUCMSCs infusion for drug‐resistant systemic lupus erythematosus patients.…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticsupporting
confidence: 59%
“…These stem cells can differentiate into the required cell types and secrete regenerative factors . hUCMSCs are save for use in children and adults . while no immunogenic rejection was observed after allogeneic transplantation .…”
Section: Umbilical Cord: From Waste Materials To Source Of Therapeuticmentioning
confidence: 99%
“…Electrophysiological brain recording offers a desirable balance of these characteristics (McPartland 2016), and, though presently less accessible in existing infrastructure, tools such as eye-tracking and wearable autonomic sensors, hold great promise because they can be mass produced at low cost. Indeed, many of these techniques are already being applied in clinical trials (Dawson et al 2017). …”
mentioning
confidence: 99%
“…The EyeGaze Tracking showed a 20% increase that the children would gaze at an actress' eyes. Mild adverse events were seen: allergic reactions to infusion, skin changes, agitation, and common childhood infections [115].…”
Section: Cell Therapymentioning
confidence: 99%
“…After 2 years, the Pentoxifylline Nausea, vomiting, low blood pressure, and headache [70] Pentoxifylline Limited to the gastrointestinal tract [72] Luteolin Increased irritability [86] Prednisolone Cushing syndrome, irritability. Gastrointestinal bleeding and hypercalcemia (both self-limited) [90] Minocycline Gastrointestinal and upper respiratory symptoms, pica, hematuria, weight gain, hyperactivity, urinary tract infection, otitis media, epistaxis, teeth staining, increased aggression, head-banging, sensitivity to light, appetite loss, and ritualistic behavior [125] Pioglitazone Transitory and self-limited elevations in white blood count, glucose levels, and liver enzymes [133] Oral human immunoglobulin Skin and subcutaneous tissue disorders [103] Oral human immunoglobulin Vomiting, skin rash [103] Intravenous immunoglobulin Mild headaches and infusion-site reactions [108] Mononuclear cells and mesenchymal stem cells Self-limited low-grade fever [110] Autologous cord blood Allergic reaction, skin changes, agitation, and childhood infections [115] Autologous bone marrow-derived mononuclear cells…”
Section: Sulforaphanementioning
confidence: 99%